Correction: Chen et al. Heteronemin Suppresses Lymphangiogenesis Through ARF-1 and MMP-9/VE-Cadherin/Vimentin. Biomedicines 2021, 9, 1109 - Hsien-Lin Chen; Yu-Chieh Su; Huang-Chi Chen; Jui-Hsin Su; Chang-Yi Wu; Shih-Wei Wang; In-Pin Lin; Chung-Yi Chen; Chien-Hsing Lee (Biomedicines)
Error in Affiliation [...]